Cevap:a+b)2=a2+2ab+b2
(a-b)2=a2-2ab+b2
* (a+b+c)2=a2+b2+c2+2(ab+ac+bc)
* (x+1)2=x2+2x.1+12=x2+2x+1
* (x-3)2=x2-2.x.3+32=x2-6x+9
* (2x-3y)2=(2x)2-2.2x.3y+(3y)2=4x2-12xy+9y2
* (x-
1
x
)2= x2-2.x.
1
x
+
1
x2
= x2-2+
1
x2
* (x+
1
x
)2= x2+2.x.
1
x
+
1
x2
= x2+2+
1
x2
(a + b)3 = a3 + 3a2b + 3ab2 + b3
(a − b)3 = a3 − 3a2b + 3ab2 − b3
* (x+2y)3= x3+3.x2.2y+3.x.(2y)2+(2y)3= x3+6x2y+12xy2+8y3
* (2a+3b)3= (2a)3+3.(2a)2.3b+3.2a.(3b)2+(3b)3= 8a3+36a2b+54ab2+27b3
* (2x-y)3= (2x)3-3.(2x)2.y+3.2x.y2-y3= 8x3-12x2y+6xy2-y3
* (3a-4b)3= (3a)3-3.(3a)2.4b+3.3a.(4b)2-(4b)3= 27a3-108a2b+144ab2-64b3
Adım adım açıklama: UMARIM YARDIMCI OLUR İYİ DERSLER :)